Evaluation of a PCR and comparison with RLB for detection and differentiation of Theileria sp MK and other Theileria and Babesia species of small ruminants - Altay, Kursat; Aktas, Munir; Dumanli, Nazir; Aydin, Mehmet Fatih (Springer, 2008)
Theileria sp. MK in sheep and goats were detected first time by polymerase chain reaction (PCR) and detection limit of PCR and reverse line blotting (RLB) were compared. A part of 18S ssu rRNA gene was amplified from blood samples that were taken from sheep and goats naturally infected with Theileria sp. MK by PCR. Detection limit of both PCR and RLB methods was one infected cell in 10(7) sheep erythrocytes. Nine hundred twenty field samples that had been tested previously by RLB were evaluated by the PCR assay. As found by RLB previously, 12 of 920 (1.30%) samples were detected as positive by PCR. Two positive PCR products, one of which was from sheep and the other from goat, were sequenced. These sequences were identical to the reported nucleotide sequence of Theileria sp. MK. It is concluded that the PCR described in this study will be useful for epidemiological studies and for discrimination between Theileria sp. MK and other Theileria species. In addition, PCR has superiority over RLB because of its ease of use and time period required.
Keywords: Infecting Small Ruminants; Polymerase-Chain-Reaction; Genetic Diversity; Eastern Turkey; Cattle; Sheep; Annulata; Identification; Lestoquardi; Piroplasms